2021
DOI: 10.34117/bjdv7n2-261
|View full text |Cite
|
Sign up to set email alerts
|

Análise Da Composição Química Do Bio-Óleo Produzido via Pirólise De Sementes De Açaí (Euterpe Oleracea, Mart) / Chemical Analysis of Bio-Oil Produced by Pyrolise of Açaí (Euterpe Oleracea, Mart) Seeds

Abstract: RESUMO Neste trabalho, a influência da temperatura na composição química (hidrocarbonetos e produtos oxigenados) do bio-óleo obtido via pirólise de sementes do Açaí (Euterpe oleracea, Mart.), um resíduo rico em lignina-celulose, foi sistematicamente investigada em escala piloto. A reação de pirólise foi realizada em reator de 143 L, operando em modo batelada a 350, 400 e 450 ºC, 1,0 atmosfera. A composição química e a análise qualitativa das funções e/ou grupos presentes no bio-óleo foram determinadas por GC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…These results were effectively modeled using a first-order exponential growth model, with an r 2 value of 1.00 for both categories. These findings align with the research conducted by de Sousa et al [32], who investigated the influence of process temperature on the concentration of hydrocarbons and oxygenates in bio-oil derived from açaí seeds using a pilot-scale pyrolysis setup. Their study, which examined temperatures of 350, 400, and 450 • C under a pressure of 1.0 atm, demonstrated that the concentration of hydrocarbons increased while the concentration of oxygenates decreased with rising temperature.…”
Section: Process Analysis 211 Effect Of Process Temperaturesupporting
confidence: 91%
See 4 more Smart Citations
“…These results were effectively modeled using a first-order exponential growth model, with an r 2 value of 1.00 for both categories. These findings align with the research conducted by de Sousa et al [32], who investigated the influence of process temperature on the concentration of hydrocarbons and oxygenates in bio-oil derived from açaí seeds using a pilot-scale pyrolysis setup. Their study, which examined temperatures of 350, 400, and 450 • C under a pressure of 1.0 atm, demonstrated that the concentration of hydrocarbons increased while the concentration of oxygenates decreased with rising temperature.…”
Section: Process Analysis 211 Effect Of Process Temperaturesupporting
confidence: 91%
“…The concentrations of phenols, esters, and ketones decrease with increasing pyrolysis temperature, showing a smooth exponential decay behavior, as shown in Figure 3. The results are according to those reported by de Sousa et al [32]. The concentration of oxygenates in bio-oil was correlated with a first-order exponential decay model, exhibiting in all the cases a rootmean-square error (r 2 ) of 1.00.…”
Section: Process Analysis 211 Effect Of Process Temperaturesupporting
confidence: 90%
See 3 more Smart Citations